Patient confidentiality, ethics and licensing in telemedicine - Yadav, H.; Wong, Y.L. (SAGE Publications, 2001)
Telemedicine is fast becoming popular in many countries in the world. It has several advantages such as being cost saving and providing better access to health care in the remote areas in many parts of the world. However, it has some disadvantages as well. One of the major problems is the problem of patients' rights and confidentiality in the use of telemedicine. There are no standard guidelines and procedures in the practice of telemedicine as yet. Both the patient and the physician are unsure of the standard of practice and how to maintain confidentiality. The patient is uncertain as to how to protect her/his rights in the use of telemedicine. The issue of litigation is also unclear as to where the physician is practicing when he/she uses telemedicine. Is she/he practicing in the country where the patient is or is the physician practicing in the country of her/his origin? These issues need to be addressed urgently so that telemedicine will have standards of ethical practice and the patient's rights and confidentiality will be protected.